The Drug Court Pharmacist: Expanding Pharmacy Practice and Addressing Substance Abuse - Laura C Palombi, PharmD; Cynthia P Koh-Knox, PharmD (University of Minnesota Libraries Publishing, 2016)
Problem solving courts, including Drug Court, were established to address substance abuse while providing an alternative to prison sentences and traditional corrections supervision. Drug Courts have been shown to reduce crime in participants and graduates, save the criminal justice and health care systems money, reduce victimization, and restore families. Pharmacists in Tippecanoe County, Indiana, and Carlton County, Minnesota, have established innovative practices as members of Drug Court teams; these practices include the provision of a variety of pharmaceutical and health-related services that other Drug Court team members are not able to provide. The role of the pharmacist on the Drug Court team deserves exploration in light of the increasing needs of problem-solving courts across the United States and the current substance abuse epidemic that unfortunately includes prescription drugs. Conflict of Interest "We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties."   Type: Idea Paper